Desarrollo de una aplicación WEB para pedidos en línea en la casa comercial Calva & Calva. - Cuenca, Danny Daniel (2009)
In an effort to achieve a research work on the influence of electronic commerce, and how it can serve as a basis for strengthening the competitive level of the companies concerned to achieve competitiveness in a market that daily demand for new and improved services, it has chosen to develop a web application for online orders. Applying online orders will enable companies to offer their products and services, so that customers, prior to the creation of a user account can access via the Internet to the services offered, as is the acquisition of a range of products. In this case Calva & Calva business which is the base company for the development of the application, is who receptará Customer's order and then proceed to despatch, delivering at home, at the time of delivery the customer must make the respective payment.